2003
DOI: 10.3390/s30900340
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Milk Quality With Disposable Taste Sensor

Abstract: A disposable screen-printed multi channel taste sensor composed of several types of lipid as transducers and a computer as data analyzer could detect taste in a manner similar to human gustatory sensation. The disposable taste sensor was used to measure the electrical potential resulted from the interaction between lipid membranes and taste substances. In the present study, two types of packaged commercial milk, the ultra high temperature (UHT) and the pasteurized milk were tested. It was found that the dispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The Mobile Crowd-Sensing Network (MCSN) is a novel cyber–physical–social system. In MCSN, humans carry smart devices with sensing and wireless communication capabilities which allow them to collect and upload data to the assessment center for large-scale sensing and community intelligence mining [3,4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The Mobile Crowd-Sensing Network (MCSN) is a novel cyber–physical–social system. In MCSN, humans carry smart devices with sensing and wireless communication capabilities which allow them to collect and upload data to the assessment center for large-scale sensing and community intelligence mining [3,4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, potentiometric based devices have also been used for milk assessment. In more detail, Sim et al [12] proposed a disposable screen-printed multi-channel potentiometric E-tongue, with several types of lipid compounds as transducers, to discriminate between fresh and spoiled UHT or pasteurized milk as well as to follow the deterioration of the milk quality when it is stored at room temperature based on PCA. Other researchers [3,13] showed that a miniaturized solid-state potentiometric E-tongue operating either in stationary or flow-through mode, together with SVM or ANN, could be successfully applied to classify UHT milk samples according to brand and fat contents (97% of correctly classified samples belonging to an external test dataset).…”
Section: Introductionmentioning
confidence: 99%
“…A disposable multichannel screen-printed lipid-based taste sensor was proposed by Sim et al , to control the quality of milk [ 25 ]. The advantages of this taste sensor are its small size, simple construction, and low cost, however, it has a response time of approximately 60 s. Thete et al developed an optochemical fluorometric microspot array to detect various kinds of alcoholic beverages [ 26 ].…”
Section: Introductionmentioning
confidence: 99%